Willingness to pay for crop insurance to adapt flood risk by Malaysian farmers: An empirical investigation of Kedah - Afroz, Rafia; Akhtar, Rulia; Fauzi, Puteri Farhana (International Journal of Economics and Financial Issues, 2017)
This study examines the factors that may affect the willingness to pay (WTP) crop insurance by Malaysian rice farmers in Kedah, Malaysia, for the adaptation of flood risk. 350 farm households are selected and a structured questionnaire is used to elicit data from the respondents. The data are analyzed with descriptive statistics and logit regression model. The average WTP for monthly crop insurance premium by the respondents is MYR 48.15 for every RM 1000 coverage/ha/season. The significant variables influencing WTP crop insurance by the farmers are the age of household head, attending the training course, farm income, and experience and farm size. From the findings of this work, it is urged that to promote crop insurance in Malaysia, the government may require a strategic policy to convince the farmers of the credibility and reliability of insurance scheme by improving farmers’ awareness and understanding of crop insurance through advertisement and training.